Development and validation of the Moral Distress in Dementia Care Survey instrument. (22nd August 2018) - Awosoga, Olu; Pijl, Em M.; Hagen, Brad; Hall, Barry; Sajobi, Tolulope; Spenceley, Shannon
Abstract: Aims: To report on the development and validation of the Moral Distress in Dementia Care Survey instrument. Background: Despite growing awareness of moral distress among nurses, little is known about the moral distress experiences of nursing staff in dementia care settings. To address this gap, our research team developed a tool for measuring the frequency, severity and effects of moral distress in nursing staff working in dementia care. Design: The research team employed an exploratory sequential mixed method design to generate items for the moral distress questionnaire. Data were collected between January 2013 – June 2014. In this paper, we report on the development and validation of the Moral Distress in Dementia Care Survey instrument. Methods: The Moral Distress in Dementia Care Survey instrument was piloted with a portion of the target population prior to a broader implementation. Appropriate statistical analyses and psychometric testing were completed. Results: The team collected 389 completed surveys from registered nurses, licensed practical nurses and healthcare aides, representing a 43.6% response rate across 23 sites. The Moral Distress in Dementia Care Survey emerged as a reliable and valid instrument to measure the frequency, severity and effects of moral distress for nursing staff in dementia care settings. The relative value of the Moral Distress in Dementia Care Survey as a measurement instrument was superseded by its clinical relevance for dementia care staff. Conclusion: The Moral Distress in Dementia Care Survey is a potentially useful tool for estimating the frequency, severity and effects of moral distress in nursing staff working in dementia care settings and for the evaluation of measures taken to mitigate moral distress. Abstract : 目标: 报道痴呆症护理测量仪器中道德困扰的发展和验证。 背景: 尽管越来越多的人意识到护士的道德困扰, 但对于护理人员在痴呆症护理环境中的道德困扰经历, 人们知之甚少。为解决这一问题, 研究小组开发了一种工具, 用以测量在痴呆症护理环境中工作的护理人员产生道德困扰的频率、严重程度和影响。 设计: 研究小组采用了探索性顺序混合法设计, 来生成道德困扰调查问卷项目。数据收集阶段为2013年1月至2014年6月。本文报道了痴呆症护理调查仪器中道德困扰的发展和验证。 方法: 在进行更为广泛的实施前, 我们在目标人群中对痴呆症护理调查仪器中的道德困扰进行了试点研究。最终完成了适当的统计分析和心理测试。 结果: 研究小组从注册护士、持照护士和医疗保健助理处收集了389份完整的调查问卷, 这相当于23处试点中有43.6%的人员给出回应。痴呆症护理调查中的道德困扰可作为一种可靠且有效的工具, 来测量痴呆症护理环境中护理人员产生道德困扰的频率、严重程度和影响。痴呆症护理调查中的道德困扰作为一种测量工具, 其与痴呆症护理人员的临床相关性取代了其相对价值。 结论: 痴呆症护理调查中的道德困扰或是评估在痴呆症护理环境中工作的护理人员产生道德困扰的频率、严重程度和影响的有用工具, 也或是评估减轻道德困扰所采取的措施的有用工具。